Motivation hos djurägare : en kvalitativ innehållsanalys - Forsman, Jasmine (SLU/Dept. of Animal Environment and Health (until 231231), 2012)
AIM The aim of this paper was to clarify some of the factors that motivates pet owners to follow advice and instructions from veterinary nurses, so called compliance.